Financial Education for Early Childhood at TK Negeri PO-5 - Uli, Nur Zarliani; Agustyawati, Dwi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Financial education for early childhood at TK Negeri PO-5 has not been directly implemented for students because parents tend to save money for their children without involving them in the process. However, the introduction of financial education should ideally start early to be beneficial in the futer. Financial education is not just about recognizing money and its denominations, but also about managing finances and saving. Community service activities are conducted at TK Negeri PO-5 using methods such as lectures, interviews and demonstrations using money and piggy banks. Evaluations results indicate that the community service activities have been successful. Students can understand and recognize the functions of money and they can manage or save money. In addition, students also enjoy participating in these activities.